International Market Diversification Strategy for Indonesian Professional Manpower Placement: A Case Study of PT. Binawan Inti Utama - Yona Demita Ganta; Andrianto Widjaja (Sanskara Ekonomi dan Kewirausahaan, 2026)
Indonesia Migrant Worker Placement Companies (P3MI) operating in the professional manpower sector face a persistent vulnerability: international market concentration. PT. Binawan Inti Utama (BIU), part of the Binawan Group ecosystem, currently concentrates placements on a small set of destination corridors (Middle East, Japan, Germany) and three core sectors (healthcare, hospitality, aviation), leaving the firm exposed to country-specific regulatory shifts, employer-side bargaining pressure, and currency volatility. At the same time, a global talent shortage is driving sustained demand across new markets, particularly in healthcare and logistics where vacancies have reached 77% and 74% respectively (ManpowerGroup, 2026). This study designs an international market diversification strategy for BIU's professional manpower business along two dimensions: geographic (destination country) and sectoral (industry segment). A qualitative case study approach was employed. Primary data were collected through in-depth interviews with directors, heads of placement programs, human capital management, and prospective migrant workers; secondary data were drawn from internal company documents, KP2MI/BP2MI statistics, and credible international sources. The analysis applied PESTEL, Porter's Five Forces, VRIO, Parenting Advantage, IFE/EFE matrices, SWOT-TOWS, the Competitive Profile Matrix (CPM), the Internal-External (IE) Matrix, the Quantitative Strategic Planning Matrix (QSPM), and the Balanced Scorecard for implementation. The IE Matrix positions BIU in Cell V (“hold and maintain”), and the QSPM ranks market penetration in existing destination corridors as the highest-priority strategy (total attractiveness score 6.78), followed by product development through new Specified Skilled Worker sectors (5.62) and market development into new destination countries (5.34). Because the three scores are close and complementary, this study positions diversification as a phased program in which market penetration funds the near-term revenue base while geographic and sectoral expansion build the medium-term growth path. The proposed design combines geographic expansion into Australia, broader European Union markets, and the Nordic region with sectoral expansion into construction, manufacturing, and non-medical caregiving under Specified Skilled Worker and equivalent schemes. Execution is enabled by activating the Binawan Group ecosystem (UnBin, BTC, LPK, BICCA), digital integration through the Vokati platform, and structured managerial capability development. The study contributes a two-dimensional diversification framework for partnership-intensive service exporters in emerging markets and an implementation-oriented Balanced Scorecard that translates diversification intent into measurable execution.